MOTIVASI SISWA KELAS VIII SMP CITA BUANA DALAM MENULIS PUISI: SEBUAH TINJAUAN PSIKOLINGUISTIK - Ekawati, Elisabeth Devitta; Tarmini, Wini (Jurnal Citra Pendidikan, 2025)
This study aims to analyze the factors influencing the motivation of eighth-grade students at SMP Cita Buana Jakarta in writing poetry using a psycholinguistic approach. A case study method was employed, with data collection techniques including semi-structured interviews and questionnaires. The findings reveal that while most students enjoy the process of writing poetry, their motivation is predominantly driven by external factors, such as teacher assignments. The main challenges faced include generating ideas and selecting appropriate words. The school environment, teachers' roles, and peer appreciation significantly impact students' motivation. The study recommends integrating creative approaches such as exploring local themes, diction games, and poetry competitions to enhance students' intrinsic motivation. Thus, poetry writing can become a more enjoyable, meaningful, and relevant activity for students.